Advanced surface-enhanced raman scattering nanoprobes for precise detection of Nitroreductase in Hypoxic tumor cells: Improving Cancer diagnosis - Xiaoyue Zhao; Ying Zhang; Chunyan Zhu; Zhihui Yang; Xiaoyuan Chu (SLAS Technology)
Nitroreductase (NTR) plays a critical role in the oxygen-deficient environment of anoxic tumor cells, and its identification is crucial for the diagnosis and treatment of cancer. This research introduces an innovative Surface Enhanced Raman Scattering (SERS) probe, created by attaching p-nitrothiophenol (p-NTP) to gold nanoparticles (Au NPs). This probe leverages the specific enzymatic reaction of NTR in hypoxic status, utilizing decreased NADH. The enzymatic activity of NTR transforms nitroaromatic compounds into aromatic amines, which is then reflected as a measurable shift in the SERS signal of the probe. This novel approach allows for the accurate quantification of NTR, with the sensitivity reaching a detection threshold of less than 0.02 μg/mL. The probe's non-toxic nature and superior biocompatibility facilitate its use for direct SERS investigations in A549 cells under reduced oxygen levels. We also applied this method to xenograft model. The results demonstrate a marked increase in NTR levels in tumor cells and tumor tissues in hypoxic conditions, highlighting the significance of this nanoprobe in enhancing cancer diagnostics, helping medical doctors making treatment decisions more swiftly and effectively.